Implications of LINC01094 for human malignancies - Wang, Yan; Yang, Yang; Zhang, Quanying; Zeng, Ying; Cai, Yilin; Luo, Haiqing; Li, Xiangyong (PeerJ, 2026)
Long non-coding RNAs (lncRNAs) constitute a large class of ribonucleic acids, participating in multiple biological events within tumor cells, especially the regulation of transcription. A growing body of literature has revealed that abnormalities of lncRNA expression could result in carcinogenesis and oncogenesis by exerting inhibition or oncogenic effects. LINC01094 is a recently identified lncRNA found to be dys-regulated in an assortment of cancer tissues and control multiple biological processes via competing endogenous RNA (ceRNA) mechanisms. Specifically, LINC01094 functions as a ceRNA to modulate tumor cell growth, invasion, and migration by regulating critical signaling pathways including PI3K/AKT, PTEN/AKT, and Wnt/β-catenin, while also exerting oncogenic effects through transcriptional regulatory networks. Numerous recently published reports have shown that LINC01094 exerts critical functions during the regulation of malignant cell growth, migrating ability, and invasiveness, thereby controlling cancer cell growth and metastasis. In this review, multiple cancer biology functions of LINC01094 documented in published literature are summarized, aiming to inspire innovations in the management of human malignancies under laboratory and clinical settings.
Keywords: Cancers; Clinical characteristics; Growth and metastasis; LINC01094; Molecular mechanisms